Theory of linear poroelasticity with applications to geomechanics and hydrogeology - Wang, Herbert (Princeton series in geophysics., 2000)
"The theory of linear poroelasticity describes the interaction between mechanical effects and adding or removing fluid from rock. It is critical to the study of such geological phenomena as earthquakes and landslides and is important for numerous engineering projects, including dams, groundwater withdrawal, and petroleum extraction. Now an advanced text synthesizes in one place, with one notation, numerous classical solutions and applications of this highly useful theory."--Publisher